Gender Equality, Climate Action and Affordable Clean Energy Practices Towards Firm Financial Performance of Oil and Gas PLCs - Baharudin, Dayana Mastura; Azmi, Nurhafizah Kamilah Mohammad; Ibrahim, Haslindar; Marimuthu, Maran; Shahimi, Suhaily (Business Management and Strategy, 2023)
The purpose of this study is to investigate the impact of the disclosure extent of the practices of gender equality, climate action and affordable and clean energy towards firm financial performance of the Top 30 Malaysia’s Oil and Gas PLCs over a five-year period from 2018 to 2022. This study employed both the conceptual and theoretical framework as the direction of this whole research, where the independent variables are SDG 5 - Gender Equality, SDG 13 - Climate Action and SDG 7 - Affordable and Clean Energy. The dependent variable is related to firm financial performance which are proxied by the Return on Asset (ROA), Return on Equity (ROE) and Tobin’s Q. The control variables are represented by Firm Leverage (LEV), Firm Age (AGE) and Firm Size (SIZE). All the variables are supported by the stakeholder theory. Purposive sampling was employed within this descriptive and quantitative study. Secondary data employed was analyzed using the quantitative content analysis and panel data regression analysis as per the STATA v.14 software. The findings reflect significance across all models of Pooled Ordinary Least Square (OLS), Fixed Effect Model (FE), and Random Effect Model (RE) where the p-value of gender equality, climate action and affordable clean energy are all 0.0000. The novelty of this research in terms of methodological significance is that the data were collected using quantitative content analysis from the integrated and annual reports of the Malaysian PLCs using three scoring indices designed for the oil and gas industry. Novelty in terms of practical significance is that the findings from this research can be applied to the oil and gas PLCs in other countries other than Malaysia.